2001
DOI: 10.1002/eqe.75
|View full text |Cite
|
Sign up to set email alerts
|

Relative displacement response spectra with pounding effect

Abstract: SUMMARYTo avoid unseating of a deck, an adequate seat length must be provided. The seat length is generally determined from a maximum relative displacement between two bridge segments. Under strong ground excitation, pounding between two decks may occur at a joint. The pounding will affect responses of two bridge segments. This research was conducted to investigate the effect of pounding on the relative displacement between two adjacent bridge segments. A simplified analytical model was developed for such a pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…A further conclusion of the DesRoches & Muthukumar [15] work is that when the natural frequency and the excitation frequency are separated the one-sided impact is accentuated, whereas, impact suppresses the response of the oscillators at resonance. At about the same time an analogous study was conducted in Japan by Ruangrassame & Kawashima [16] who proposed the so-called 'relative displacement response spectrum with pounding effect'. Contrary to the work of DesRoches & Muthukumar the work of Ruangrassame & Kawashima concluded that in addition to the stiffness ratio and the period ratio, the mass ratio of the two oscillators governs appreciably the response.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A further conclusion of the DesRoches & Muthukumar [15] work is that when the natural frequency and the excitation frequency are separated the one-sided impact is accentuated, whereas, impact suppresses the response of the oscillators at resonance. At about the same time an analogous study was conducted in Japan by Ruangrassame & Kawashima [16] who proposed the so-called 'relative displacement response spectrum with pounding effect'. Contrary to the work of DesRoches & Muthukumar the work of Ruangrassame & Kawashima concluded that in addition to the stiffness ratio and the period ratio, the mass ratio of the two oscillators governs appreciably the response.…”
Section: Introductionmentioning
confidence: 89%
“…[15], [8], [16]) The purpose of the following discussion is to reassess the significance of mass ratio (Π 6 ) on the response of oscillators with unilateral contact. Figure 8 and Figure 9 show the response spectra for constant frequency ratios, Π 5 = ω 0 / ω 1 , and dimensionless gaps, Π 3 = δω p 2 /α p , but different mass ratios, Π 6 = m 0 / m 1 , of the two oscillators.…”
Section: The Role Of M 0 /M 1 Ratiomentioning
confidence: 99%
“…The ÿrst one applies the classical theory of impact, called stereomechanics, which is based on the laws of conservation of energy and momentum and does not consider transient stresses and deformations in the impacting bodies [21][22][23]. The theory focuses on determination of postimpact velocities of colliding bodies based on the approaching velocities prior to contact and a coe cient of restitution which accounts for the energy dissipation during impact incorporating response non-linearities.…”
Section: Classical Theory Of Impactmentioning
confidence: 99%
“…However, as one of the important components of bridge, the aseismic behavior of expansion joints have long been neglected by researchers (Saiidi, 1996;Kawashima, 2000;Ruangrassamee, 2001;Zanardo, 2001;DesRoches, 2002) and the past papers have given importance to the enhancement of durability, cold resistance and noise-resistance of expansion joints. For example, Ancich et al studied the dynamic anomalies of the modular bridge expansion joints (Ancich, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%